The Effect of Yeast Starter Variations on the Quality of Virgin Coconut Oil (VCO) Using the Fermentation Method - Dine Agustine; Meylika Mawar Gumilang; Nia Komalasari (Helium: Journal of Science and Applied Chemistry, 2021)
Virgin Coconut oil (VCO) is a coconut processed product that has high benefits and economic value. One of the methods of making VCO is the fermentation method. The purpose of this study was to determine the effect of the percentage of 3 types of yeast (starter yeast tape, starter yeast bread (Saccharomyces cerevisiae) and tempeh yeast (Rhizopus sp) on the quality of VCO produced in terms of volume, viscosity, organoleptic(color, distinctive coconut odor) and chemical test (moisture content, acid number, free fatty acid, peroxide number) The manufacturing method used was the fermentation method by varying the percentage ratio of starter for each yeast by 3%, 6%, and 9%. The results showed the addition of starter percentage Yeast has an effect on the volume of VCO produced, moisture content, acid number, free fatty acids, and viscosity These results have met the quality standards according to SNI 7381: 2008 and APCC (Asian and Pacific Coconut Community).